Implementation Of Complete Systematic Land Registration Services During The Covid-19 Pandemic - Fitri Adhi Nugroho; Umar Ma'ruf (Universitas Islam Sultan Agung, 2021)
The purpose of this study is as follows: To find out the problems faced in PTSL services during the Covid-19 Pandemic at the Pekalongan City Land Office, to find out and analyze the implementation of PTSL services during the Covid-19 Pandemic at the Pekalongan City Land Office. This study uses a sociological juridical approach. Based on the results of the study, it can be concluded: (1) Existing Problems in PTSL Services During the Covid-19 Pandemic Period at the Land Office of Pekalongan City, including: (a) The factor of social distancing so it is not allowed to carry out measurements as before the pandemic, thus progress of implementation becomes hampered, while there is still a PTSL completion target that must be met, (b) The budget factor of the ministry of ATR/BPN is saved for the needs of handling the pandemic, so that the target is reduced / unit costs are lowered / there is even work in the implementation of PTSL that cannot be paid, (c ) The time period for the announcement of physical data and juridical data differs between the Government Regulation and the Ministerial Regulation concerning PTSL, (d) The factor of law enforcement facilities,the presence of an invalid resident e-KTP has been brought to the sub-district office but is still not recorded in the KKP application so that the efforts made are to coordinate with the Population and Civil Registry Office of Pekalongan City, (e) The factor of low public interest in participating in the implementation of PTSL activities from from the beginning until the issuance of certificates in 2020 there were 504 certificates printed, 504 certificate signatures, and G. Scan BT PTSL 2020, (2) Implementation of PTSL Services During the Covid-19 Pandemic Period at the Land Office of Pekalongan City, the results namely Print Certificate: 504 fields, Certificate Signature: 504 fields, and G. Scan BT PTSL 2020: 504 fields.